ANALISIS KELEMBAGAAN PASAR INPUT DAN OUTPUT USAHA TERNAK RAKYAT - HENDAYANA, RACHMAT; WALLY, FRITS (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
This study aims to investigate the characteristic of input and output market institutions for smallholder livestock and also identify factors influencing the market institution performance in smallholder livestock. Data are collected through unstructured interview using Participatory Rural Appraisal (PRA) with focus group discussion at Nabire in FY 2003 covering 30 selected livestock farmers and some traders as interviewed respondent. Data analysis conducted using qualitative and quantitative description, and research result reveals that: (a) input – output market institutions have important role as determinant factors in smallholder livestock especially the correlation of livestock farmer earnings, (b) Bargaining position of farmer very weak in marketing of livestock output, because the market structure of tending to oligopoly, (c) Performance of livestock market not only influenced by internal factor, however is also determined factor of external, (d) Motivation for form of mutual profiting partner between livestock farmer and other party is needed to improve performance of input-output marketing of livestock. .
Keywords: Smallholder Livestock, Input-Output Market, Institutions, Nabire